CECI N´EST PAS UNE PIPE: A REFLECTION ON THE RELATIONSHIP BETWEEN WORDS AND IMAGES IN GENERATIVE ARTIFICIAL INTELLIGENCE AND ITS USE IN ARTISTIC EDUCATION. (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2024)
These pages narrate a practice carried out during several sessions in the context of the subject Digital Technologies, which I teach at the university level of the Bachelor of Arts, as well as the reflections arising in the light of its results. In the context of the final personal research project carried out in the afore mentioned subject, small practical research in Artificial Intelligence generative systems was proposed (henceforth IA) of the type of text-image (text to images), as well as an invitation to students to use the results obtained in their research to conceive and create working materials and carry out their project. They were called for a critical reflection on the relationship between the texts introduced and the images generated and by extension, between the images and the words allegedly describing them. These pages relate the procedure used, some reflections and the analysis of a case study of the work of one of the students.
Keywords: Generative Artificial Intelligence; artistic practice; digital technologies; text-to -image relationship